Teaching Social Justice Through Shakespeare - Eklund, Hillary (Edinburgh University Press, 2023)
New ideas for teaching contemporary social justice through Shakespeare and Renaissance literature. Describes innovative and portable teaching methods informed by recent scholarship in early modern literature, cultural studies, and critical pedagogy. Offers strategies for effective teaching and advocacy amidst the growing cultural and economic complexities of higher education. Demonstrates the relevance of historical literary study to contemporary cultural conversations, especially those about social justice. Historicizes the malicious whitening" of Shakespeare and European culture, recognizing instead multiple, multicultural, accessible Shakespeares. Presents Shakespeare’s plays as a common corpus of great value to democratic conversations in widely divergent contexts. Gives educators language for promoting the virtue of humanistic inquiry and when higher education is on the defensive. This book is for teachers who want to heighten the intellectual impact of their courses by using their classrooms as a creative space for social formation and action. Its twenty-one chapters provide diverse perspectives on Shakespeare and early modern literature that engage innovation, collaboration, and forward-looking practices. They model ways of mobilizing justice with early modern texts and claim the intellectual benefits of integrating social justice into courses. The book reconceives the relationship between students and Renaissance literature in ways that enable them – and us – to move from classroom discussions to real-life applications."